On‐Surface Synthesis of a Dicationic Diazahexabenzocoronene Derivative on the Au(111) Surface. (21st October 2021) - Biswas, Kalyan; Urgel, José I.; Xu, Kun; Ma, Ji; Sánchez‐Grande, Ana; Mutombo, Pingo; Gallardo, Aurelio; Lauwaet, Koen; Mallada, Benjamin; de la Torre, Bruno; Matěj, Adam; Gallego, José M.; et al.
Abstract: The atomically precise control over the size, shape and structure of nanographenes (NGs) or the introduction of heteroatom dopants into their sp 2 ‐carbon lattice confer them valuable electronic, optical and magnetic properties. Herein, we report on the design and synthesis of a hexabenzocoronene derivative embedded with graphitic nitrogen in its honeycomb lattice, achieved via on‐surface assisted cyclodehydrogenation on the Au(111) surface. Combined scanning tunnelling microscopy/spectroscopy and non‐contact atomic force microscopy investigations unveil the chemical and electronic structures of the obtained dicationic NG. Kelvin probe force microscopy measurements reveal a considerable variation of the local contact potential difference toward lower values with respect to the gold surface, indicative of its positive net charge. Altogether, we introduce the concept of cationic nitrogen doping of NGs on surfaces, opening new avenues for the design of novel carbon nanostructures. Abstract : A hexabenzocoronene derivative embedded with graphitic nitrogen in its honeycomb lattice is prepared by on‐surface assisted cyclodehydrogenation on the Au(111) surface. Combined scanning tunnelling microscopy/spectroscopy and non‐contact atomic force microscopy investigations unveil the chemical and electronic structures of the obtained dicationic nanographene.